Learning analytics based feedback and recommendations in flipped classrooms: an experimental study in higher education - Üstün, Ahmet Berk; Zhang, Ke; Karaoğlan Yılmaz, Fatma Gizem; Yılmaz, Ramazan; Yılmaz, Ramazan; Yılmaz, Ramazan; Karaoğlan Yılmaz, Fatma Gizem; Üstün, Ahmet Berk (Routledge Journals, Taylor & Francis Ltd, 2023)
This mixed-method pretest/post-test experimental study examined the effect of learning analytics (LA)-based interventions on students' academic achievement and self-regulatory skills, and explored students' perceptions of such interventions in flipped classrooms (FC). Sixty-two college students from an introductory computer course were randomly assigned to the experimental or control group, with 31 participants in each condition. In the following 10 weeks, LA-based personalized interventions, including both visual feedback and written recommendations were provided to those in the experimental group on a weekly basis. Quantitative analyses found significant improvements in students' academic achievement as well as their self-regulated learning skills in the treatment group. Consistently, students' comments and feedback confirmed that LA-based interventions were effective in promoting self-regulated learning in FC. The researchers discuss both practical and research implications in FC and in online learning, provide recommendations for the design and advancement of LA-based interventions, and suggest future directions for LA research in higher education.
Keywords: Learning Analytics; Personalized Intervention; Self-Regulated Learning; Flipped Classroom; Experimental Study